2014
DOI: 10.1111/ejn.12486
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondins 1 and 2 are important for afferent synapse formation and function in the inner ear

Abstract: Thrombospondins (TSPs) are a family of secreted extracellular matrix proteins that have been shown to be involved in the formation of synapses in the central nervous system. In this study, we show that TSP1 and TSP2 are expressed in the cochlea, and offer the first description of their putative roles in afferent synapse development and function in the inner ear. We examined mice with deletions of TSP1, TSP2, and both (TSP1/2), for inner ear development and function. Immunostaining for synaptic markers indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…This seems unlikely, because an absence of the presynaptic cytomatrix protein bassoon (36), Ca V β 2 (37), or harmonin (27,28) in IHCs disorganizes the Ca V 1.3 channels without affecting the postsynaptic clustering of glutamate receptors. As an alternative hypothesis, clarin-1 may be a member of pre-and postsynaptic membrane focal adhesion complexes at the IHC ribbon synapse, possibly interacting with proteins known to be involved in the extracellular matrix at neuronal synapses, such as thrombospondins (38), or in membrane-membrane synaptic adhesion, such as Eph/ephrins, cadherins, and the neurexin the Rosenthal's canals of control, Clrn1 ex4-/-, and Clrn1 ex4fl/fl Myo15-Cre +/-mice on P24-P30 ( Figure 12E). Neuron density in the mid-base region decreased from 346.8 ± 16.7 neurons per 1,000 μm 2 (n = 4 cochleae from 3 mice) in controls to 259.6 ± 8.9 neurons per 1,000 μm 2 (n = 8 cochleae from 4 mice) in Clrn1 ex4-/-mice (P < 0.001, mean ± SD; ANOVA, post hoc Holm-Sidak test; Figure 12E).…”
Section: Hearing Rescue By Virus-mediated Gene Transfer Into the Ihcsmentioning
confidence: 99%
“…This seems unlikely, because an absence of the presynaptic cytomatrix protein bassoon (36), Ca V β 2 (37), or harmonin (27,28) in IHCs disorganizes the Ca V 1.3 channels without affecting the postsynaptic clustering of glutamate receptors. As an alternative hypothesis, clarin-1 may be a member of pre-and postsynaptic membrane focal adhesion complexes at the IHC ribbon synapse, possibly interacting with proteins known to be involved in the extracellular matrix at neuronal synapses, such as thrombospondins (38), or in membrane-membrane synaptic adhesion, such as Eph/ephrins, cadherins, and the neurexin the Rosenthal's canals of control, Clrn1 ex4-/-, and Clrn1 ex4fl/fl Myo15-Cre +/-mice on P24-P30 ( Figure 12E). Neuron density in the mid-base region decreased from 346.8 ± 16.7 neurons per 1,000 μm 2 (n = 4 cochleae from 3 mice) in controls to 259.6 ± 8.9 neurons per 1,000 μm 2 (n = 8 cochleae from 4 mice) in Clrn1 ex4-/-mice (P < 0.001, mean ± SD; ANOVA, post hoc Holm-Sidak test; Figure 12E).…”
Section: Hearing Rescue By Virus-mediated Gene Transfer Into the Ihcsmentioning
confidence: 99%
“…Presynaptic neurexins are anchored at the active zone, whereas neuroligins are anchored at the postsynaptic density (Südhof, 2008). Ablation of all three neurexin isoforms led to a marked reduction of presynaptic Ca v 2.2 currents in neocortical neurons (Missler et al, 2003), but the mechanism for this link is unclear. If neurexins/neuroligins are expressed at the IHC synapse, which is unknown so far, they may be responsible for the principal organization of the synapse, whereas ␣ 2 ␦2 might contribute to fine-tuning the apposition of clustered Ca v 1.3 channels and postsynaptic elements, such as GluA4 and PSD-95, for reducing reaction times (Figs.…”
Section: ␣ 2 ␦ Subunits In Hair Cellsmentioning
confidence: 99%
“…8). Recently, the extracellular matrix proteins thrombospondin 1 and 2 have been shown to be required for proper IHC synaptogenesis (Mendus et al, 2014). ␣ 2 ␦1 has been shown to act as a receptor for thrombospondins independently of its contribution to Ca 2ϩ channel function (Eroglu et al, 2009), and ␣ 2 ␦2 might have a similar function.…”
Section: ␣ 2 ␦ Subunits In Hair Cellsmentioning
confidence: 99%
“…TSP-1can be distinctively regulated by Rac pathway leading to increased ROS production. TSP-1 has an important role in platelet adhesion to damaged endothelium inhibiting from nitric oxide (NO)-induced vasodilation [45] and tissue perfusion in ischemic rat model [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Navarro et al showed that a pro-angiogenic shift in plasma was associated with mild short-term neurological deficit while an acute anti-angiogenic status [47] that was mainly determined by a high level endostatin and TSP-1 was associated with worse long-term functional outcomes. [45,47] Liauw et al in a study on knockout (KO) mice by unilateral occlusion of the common carotid artery (CCA) and the distal middle cerebral artery showed that loss of Thrombospondin-1/2 impairs behavioral recovery, synaptic recovery and axonal sprouting after stroke [48]. Based on evidence, TSP-1 released from oxLDL-activated platelets can lead to some cerebrovascular events.…”
Section: Discussionmentioning
confidence: 99%